1998
DOI: 10.1038/sj.onc.1202129
|View full text |Cite
|
Sign up to set email alerts
|

EWS/FLI1 up regulates mE2-C, a cyclin-selective ubiquitin conjugating enzyme involved in cyclin B destruction

Abstract: The EWS/FLI1 fusion gene found in Ewing's sarcoma and primitive neuroectodermal tumor, is able to transform certain cell lines by acting as an aberrant transcription factor. The ability of EWS/FLI1 to modulate gene expression in cells transformed and resistant to transformation by EWS/FLI1, was assessed by Representational Di erence Analysis (RDA). We found that the cyclin selective ubiquitin conjugase murine E2-C, was up regulated in NIH3T3 cells transformed by EWS/FLI1 but not in a nontransformed NIH3T3 clon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
58
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 17 publications
3
58
0
2
Order By: Relevance
“…Based upon its action as a transcription factor, it is reasonable to think that EWS-FLI1 may deregulate expression or alter selection of FLI1 target genes. Several putative EWS-FLI1 regulated genes have been identified mostly in heterologous systems, only few of which might have transforming potential by themselves (Kovar et al, 1996;Thompson et al, 1996;May et al, 1997;Arvand et al, 1998;Hahm et al, 1999;Dauphinot et al, 2001;Matsumoto et al, 2001;Zwerner and May, 2001;Lessnick et al, 2002;Fukuma et al, 2003). Results obtained with an EWS-FLI1 mutant lacking a functional ets DNA-binding domain suggest that EWS-FLI1 may have additional, transcriptionindependent functions in the cellular transformation process (Jaishankar et al, 1999;Welford et al, 2001).…”
Section: Introductionmentioning
confidence: 93%
“…Based upon its action as a transcription factor, it is reasonable to think that EWS-FLI1 may deregulate expression or alter selection of FLI1 target genes. Several putative EWS-FLI1 regulated genes have been identified mostly in heterologous systems, only few of which might have transforming potential by themselves (Kovar et al, 1996;Thompson et al, 1996;May et al, 1997;Arvand et al, 1998;Hahm et al, 1999;Dauphinot et al, 2001;Matsumoto et al, 2001;Zwerner and May, 2001;Lessnick et al, 2002;Fukuma et al, 2003). Results obtained with an EWS-FLI1 mutant lacking a functional ets DNA-binding domain suggest that EWS-FLI1 may have additional, transcriptionindependent functions in the cellular transformation process (Jaishankar et al, 1999;Welford et al, 2001).…”
Section: Introductionmentioning
confidence: 93%
“…These observations have suggested that EWS-FLI-1 transforms cells through the aberrant activation of speci®c target genes. Indeed, genes upregulated by EWS-FLI-1 have been identi®ed through di erential expression screening between EWS-FLI-1-transformed and normal NIH3T3 cells May et al, 1997;Arvand et al, 1998). However, a direct role of EWS-FLI-1 on transcriptional activation of these genes has not been unambiguously demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Using a variety of techniques and systems, several EWS/FLI1 target genes have been identified. Among them, c-myc, 13,14 cyclin D1, 14 CD99, 11 Id2, 14,15 Tenascin-C, 16 mE2-C, 17 PDGF-C, 18 EAT-2, 19 Manic Fringe, 20 uridine phosphorylase, 21 COL11A2 22 or PIM3 23 have been shown to be up-regulated by EWS/FLI1 or EWS/ERG oncoproteins, while the TGF-b type II receptor, 24,25 p57 KIP2 , 13 p21 WAF1/CIP1 26 and IGFBP3 9 are down-regulated. However, the exact mechanism of tumorigenesis mediated by EWS/ETS remains unclear.…”
mentioning
confidence: 99%